Aflasafe Biocontrol Products to Reduce Aflatoxin in Maize and Groundnut are Registered in Ten African Countries and Available at 92 Distribution Points in Nine Countries - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
In 2020, Malawi became the tenth country where Aflasafe products are registered, bringing the total number of registered Aflasafe products to 14. Registration is critical for scale-up of Aflasafe. More private companies have started manufacturing and distributing Aflasafe products, making them available to thousands of farmers. To date, Aflasafe is available at 92 distribution points across nine countries. Private sector-led demonstrations have shown 98% effectiveness of Aflasafe in farmers’ fields in Nigeria. Companies are bringing Aflasafe closer to users.